Desacidificação de frações destiladas de produto líquido orgânico do craqueamento termo-catalítico de óleos vegetais via adsorção em y-alumina e lama vermelha ativada - COSTA, Karen Marcela Barros da (Universidade Federal do Pará, 2017)
This paper studied the adsorption of residual free fatty acids (carboxylic acids) present in distilled fractions from the Liquid Organic Product (PLO) obtained by thermal catalytic cracking of vegetable oil. The objective was to deacidification of distilled fractions obtained from the distillation of the PLO. The experiments were performed using different distilled fractions using three different adsorbents, y-Alumina, Red Mud Thermally activated (400 °C) and Red mud chemically activated with solutions of HCl in different concentrations (0.25, 1 and 2M). The adsorbent capacity relative to adsorption of free fatty acids was evaluated by means of kinetic studies, measuring the change in concentration of free fatty acids present before and after adsorption by determining the Acid Number. The results indicated that increasing the initial concentration of acids decreases the adsorption capacity of the adsorbent, showing that the process is less effective at higher concentrations. For experiments with different percentages of adsorbents seen that when using 0.5% adsorbent to obtain greater efficiency in the removal of fatty acids, which decreases with increasing percentage of adsorbent. The most efficient adsorbent was red mud activated with 1M HCl, which was obtained a reduction of 98% of the fatty acids to a sample with an initial acid number of 4 mg KOH/g. Mathematical modeling indicated that the kinetic model that best represents the process was the Pseudo Second- Order. Therefore, the results show that the adsorbents used are mostly effective in the removal of free fatty acids and the initial concentration of acids in the sample has a direct effect on the performance of adsorption thereof.